The Role of Financial Literacy in Improving Financial Well-being - Rahayu, Selvia; Yanto, Heri; Wahyudin, Agus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the role of financial knowledge, financial attitudes, and financial behavior as components of financial literacy in influencing the improvement of financial well-being of economics education students. Through questionnaires measured on a Likert scale, this study collected data from 342 economics education students as a research sample determined based on proportional random sampling at three state universities in Central Java. The results of descriptive analysis show that financial knowledge, financial behavior, and financial attitudes are classified in the good category, while financial well-being is in the moderate category. Structural Equaition Modeling (SEM) analysis shows 26% Financial well-being is influenced by financial knowledge, financial attitudes and financial behavior. The results of hypothesis testing of the three variables have a significant positive effect on financial well-being.